Religiositas, Kecerdasaan Emosi, dan Tawadhu pada Mahasiswa Pascasarjana - Yola Tiaranita; Salma Dias Saraswati; Fuad Nashori (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2017)
Abstract: The aim of this research is to find out the effect of religiosity and emotional intelligence to tawadhu in post-graduate students of UII. The hypothesis of this research is there is posotive correlation between religiousity and emotional intelligence with tawadhu. The subject of this research are 117 post-graduate students of UII. The questionnaire used in this research is Islamic Humility Scale, Religiousity Scale, and Emotional Intelligence Scale. Based on double-regression in SPSS version 16, there is a positive correlation between religiousity and emotional intelligence to tawadhu with signification value of 0,000 (p0,05) and F score of 14,294.Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh variable-variabel religiositas dan kecerdasan emosi terhadap sikap tawadhu mahasiswa pascasarjana. Hipotesis penelitian adalah ada korelasi yang positif antara religiositas dan kecerdasan emosi dengan sikap tawadhu. Skala yang digunakan adalah Skala Tawadhu, Skala Kecerdasan Emosi, dan Skala Religiositas. Subjek penelitian ini berjumlah 117 mahasiswa pascasarjana. Berdasarkan uji regresi ganda, diketahui bahwa terdapat korelasi positif antara religiositas dan kecerdasan emosi dengan sikap tawadhu dengan tingkat signifikansi sebesar 0,000 (p 0,05) dan F sebesar 14,294.